Supporting High Quality Teacher Preparation: Developing a Mentoring Program for New and Early Career Special Education Faculty - Harriet J Bessette; Katie Bennett (The Advocate, 2019)
As any new or early career faculty member in the academy can attest, the early days of one’s career in higher education can be daunting, often evoking feelings of unsteadiness, tentativeness, and low self-efficacy. Despite knowing the landscape, academic neophytes are required to navigate the social and political rungs, negotiate participation on university, college, and department committees, develop and/or enhance their research niche, and demonstrate uncompromising proficiency as a teacher, mentor, supervisor and advisor. This paper explores strategies and principles that were adopted by one department within a teacher preparation program to establish a mentoring program for new and/or early career special education faculty. A major assumption we put forth in this paper is that faculty mentoring is no longer an academic frill in academe, but rather a necessary way in which we build and foster high quality teacher preparation within a complex field.
Keywords: Mentoring; New Faculty; Special Education